1994
DOI: 10.1007/bf01321060
|View full text |Cite
|
Sign up to set email alerts
|

Pestiviruses isolated from pigs, cattle and sheep can be allocated into at least three genogroups using polymerase chain reaction and restriction endonuclease analysis

Abstract: A polymerase chain reaction-based assay capable of detecting a broad range of pestiviruses from pigs, cattle, or sheep was developed. Of six sets of primers selected from different parts of the pestivirus genome, the best results were provided by a pair from the highly conserved 5' non-coding region which gave amplification with all 129 isolates tested. This panel consisted of 33 isolates from pigs, 79 from cattle, and 17 from sheep. Differentiation between the viruses was achieved by cutting the PCR-amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
353
2
12

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(369 citation statements)
references
References 43 publications
2
353
2
12
Order By: Relevance
“…The fact that pestiviruses are serologically cross-reactive and, at the same time, antigenically and genetically diverse [11], makes this suggestion feasible. It has been observed that, due to the genetic differences, the established pan-pestivirus PCR, using primer-pair 324/326 [16] might fail to detect 'HoBi'-like viruses [13]. Moreover, the serological cross-reactivity complicates differentiation through serological assays, as illustrated by the results of our VN studies.…”
Section: Seramentioning
confidence: 88%
“…The fact that pestiviruses are serologically cross-reactive and, at the same time, antigenically and genetically diverse [11], makes this suggestion feasible. It has been observed that, due to the genetic differences, the established pan-pestivirus PCR, using primer-pair 324/326 [16] might fail to detect 'HoBi'-like viruses [13]. Moreover, the serological cross-reactivity complicates differentiation through serological assays, as illustrated by the results of our VN studies.…”
Section: Seramentioning
confidence: 88%
“…A BVDV Antigen ELISA (HerdCheck BVDV Ag/Serum Plus, IDEXX GmbH, Germany) was performed on all blood samples according to the manufacturer's instructions. All results of the Antigen ELISA were verified by RT-PCR as described by Vilcek et al (1994). Blood samples were drawn by jugular vein puncture two weeks and four weeks after birth for validation of the diagnosis and for further investigations.…”
Section: Methodsmentioning
confidence: 99%
“…RT-PCR was carried out on lysed PBMCs (peripheral blood mononuclear cell pellets) of all sheep blood samples, on the blood sample drawn four weeks after birth and organ samples of the calf (lung, kidney, spleen and liver) available after culling (Krametter-Froetscher et al, 2007a). The primers 324 and 326 (Vilcek et al, 1994) amplify a conserved domain at the 5'-end of the viral genome of 288 bp in length.…”
Section: Pestivirus Investigation In a Mixedmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, viral RNA was extracted from 915 clinical samples (672 whole bloods, 150 feces, 93 nasal swabs) using an RNeasy Mini Kit (Qiagen, Valencia, CA, USA). RT-PCR procedures were performed in a one-tube system using the pan-pestivirus primer pair V324/V326; this system amplifies a portion of the 5'-UTR of pestivirus genomes (Vilcek et al, 1994). The amplified 297-bp DNA fragment was purified using an Agarose Gel DNA Extraction Kit (INtRON, Daejeon, Korea) and subcloned into the vector pGEM-T (Promega, Madison, WI, USA) according to the manufacturer's instructions.…”
Section: Elisa and Rt-pcrmentioning
confidence: 99%